PERK-Mediated Unfolded Protein Response Signaling Restricts Replication of the Tick-Borne Flavivirus Langat Virus - Lewy, Tyler G. (Viruses, 2020)
The unfolded protein response (UPR) maintains protein-folding homeostasis in the endoplasmic reticulum (ER) and has been implicated as both beneficial and detrimental to flavivirus infection. Protein kinase R (PKR)-like endoplasmic reticulum kinase (PERK), a sensor of the UPR, is commonly associated with antiviral effects during mosquito-borne flavivirus (MBFV) infection, but its relation to tick-borne flavivirus (TBFV) infection remains largely unexplored. In this study, we identified changes in UPR and autophagic activity during Langat virus (LGTV) infection. LGTV robustly activated UPR and altered autophagic flux. Knockdown of endogenous PERK in human cells resulted in increased LGTV replication, but not that of closely related Powassan virus (POWV). Finally, on examining changes in protein levels of components associated with UPR and autophagy in the absence of PERK, we could show that LGTV-infected cells induced UPR but did not lead to expression of C/EBP homologous protein (CHOP), an important downstream transcription factor of multiple stress pathways. From these data, we hypothesize that LGTV can antagonize other kinases that target eukaryotic initiation factor 2α (eIF2α), but not PERK, implicating PERK as a potential mediator of intrinsic immunity. This effect was not apparent for POWV, a more pathogenic TBFV, suggesting it may be better equipped to mitigate the antiviral effects of PERK.